Hubungan Status Gizi Ibu Bersalin dengan Kejadian Berat Badan Lahir Rendah (Bblr) - Asfarina Puspanagara; Yulia Nur Khayati (Journal of Holistics and Health Science, 2021)
Low Birth Weight (LBW) is the first cause of infant mortality in West Java. Babies born with LBW need to get serious treatment, because in these conditions babies are easily distracted. Factors that influence the occurrence of LBW are age, nutritional status, pregnancy distance and maternal parity (Manuba, 2010). The purpose of this study was to determine the relationship between maternal nutritional status and the incidence of low birth weight (LBW). This study used a descriptive analytic using a cross sectional approach. The research was conducted in August 2020 - December 2020 at RSIA dr. Djoko Pramono. The sample of this study were all deliveries at RSIA dr. Djoko Pramono from August-16 October 2020, totaling 182. Data collection techniques with secondary data were arranged using a master table. The results of the study were analyzed bivariately using the chi Square test. Based on the results of statistical analysis with chi square, it was found that there was a significant relationship between nutritional status and the incidence of LBW, with a p value of 0.000 (<0.05), OR = 16.684. Women because they will conceive and give birth and so that there is no further deficiency of pregnancy status, so as to reduce the level of morbidity and mortality of infants. Abstrak Bayi dengan Berat Badan Lahir Rendah (BBLR) merupakan penyebab pertama kematian bayi di Jawa Barat. Bayi yang lahir dengan BBLR perlu mendapatkan penanganan yang serius, karena pada kondisi tersebut bayi mudah sekali mengalami gangguan. Faktor yang mempengaruhi terjadinya BBLR yaitu umur, status gizi, jarak kehamilan dan paritas ibu (Manuba, 2010). Tujuan penelitian ini untuk mengetahuiubungan status gizi ibu dengan kejadian Berat Badan Lahir Rendah (BBLR). Penelitian ini menggunakan desain diskriptif analitik dengan menggunakan pendekatan cross sectional. Populasi Penelitian ini adalah ibu bersalin pada Agustus 2020 – Desember 2020 di RSIA dr. Djoko Pramono. Sampel penelitian ini adalah seluruh ibu bersalin di RSIA dr. Djoko Pramono dari bulan Agustus-16 Oktober 2020 yang berjumlah 182. Teknik pengumpulan data dengan data sekunder yang disusun menggunakan master table dan dianalisis menggunakan chi square. Hasil Penelitian terdapat hubungan yang signifikan antara status gizi dengan kejadian BBLR, dengan hasil p value 0.000 (< 0,05) OR = 16,684. Saran bagi pasien yaitu diharapkan untuk pasien agar lebih maksimal memperhatikan asupan makanan (status gizi) terutama .